2009
DOI: 10.1002/pssc.200982555
|View full text |Cite
|
Sign up to set email alerts
|

Structural perfection of InGaN layers and its relation to photoluminescence

Abstract: The relation between structural perfection and optical properties of InGaN with 10% In are discussed. Transmission Electron Microscopy, X‐ray diffraction and Rutherford backscattering spectrometry measurements show that only strained layers with a thickness not exceeding 100 nm are defect free and In concentration is lower than the nominal value. Extension of layer thickness leads to layer sequestration into sublayers with different In contents and the formation of planar defects as a result of layer relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Generally, a thicker thin film will lead to division of layer into sublayers with different In contents. [13][14][15] The thick In x Ga 1Àx N film consists of three different structural phase: an In-rich InGaN region on the surface, a region free from the In-rich InGaN phase in the middle, and an InGaN/GaN interface region on the bottom of the film. 16 Herein, we found the In-rich InGaN layer had a negative effect on photocurrent of In 0.20 Ga 0.80 N electrode due to surface recombination.…”
mentioning
confidence: 99%
“…Generally, a thicker thin film will lead to division of layer into sublayers with different In contents. [13][14][15] The thick In x Ga 1Àx N film consists of three different structural phase: an In-rich InGaN region on the surface, a region free from the In-rich InGaN phase in the middle, and an InGaN/GaN interface region on the bottom of the film. 16 Herein, we found the In-rich InGaN layer had a negative effect on photocurrent of In 0.20 Ga 0.80 N electrode due to surface recombination.…”
mentioning
confidence: 99%
“…Recently we also demonstrated that structural perfection of InGaN changes with the layer thickness even for nominal In concentrations as small as 10% [3]. A nearly defect free, strained layer at the interface and a relaxed, defective layer with a high density of structural defects and surface corrugation are observed.…”
Section: Introductionmentioning
confidence: 72%
“…A JEOL 3010 with 300 keV accelerating voltage and a resolution of 2.4 Å, JEOL CM300 with sub-Angstrom resolution and TEAM 0.5 for HAADF Zcontrast STEM high resolution studies have been used. 3 Results and discussion Our earlier studies using XRD [3] showed a sharp intense GaN peak and a broad InGaN peak which started to split for layers thicker than 200 nm. This resulted from the formation of sub-layers with different c parameters, indicating the onset of relaxation in the InGaN layer and different Indium concentration in the sub-layers.…”
Section: Contributed Articlementioning
confidence: 91%
“…Symbols in Fig. 3 show the experimental data on CT collected earlier [24][25][26][27][28][29][30][31][32] and borrowed additionally from Ref. 33.…”
Section: Dislocations In Ingan/gan Heterostructuresmentioning
confidence: 99%